GENDER FEATURES OF SPEECH BEHAVIOUR IN ENGLISH COMMUNICATION (World Conference on Social Sciences, Law and Public Policy, 2026)
Speech behaviour is a complex phenomenon that reflects not only linguistic competence but also social, psychological, and cultural characteristics of individuals. Modern linguistic studies increasingly focus on the relationship between language use and gender. Gender differences in communication are manifested in conversational strategies, speech acts, politeness forms, interruption patterns, and reactions to compliments. This paper examines the gender-specific features of speech behaviour in English communication based on pragmatic and sociolinguistic approaches.
Keywords: Speech behaviour, gender, communication, pragmatics, speech acts, conversational strategies, politeness